Electronic structure basis for enhanced overall water splitting photocatalysis with aluminum doped SrTiO3 in natural sunlight. Issue 4 (19th March 2019) - Zhao, Zeqiong; Goncalves, Renato V.; Barman, Sajib K.; Willard, Emma J.; Byle, Edaan; Perry, Russell; Wu, Zongkai; Huda, Muhammad N.; Moulé, Adam J.; Osterloh, Frank E.
Abstract : Aliovalently Al 3+ doped strontium titanate enables overall water splitting in type 1 baggie particle suspension reactors in direct sunlight. Abstract : Overall water splitting with photocatalyst particles presents a potentially cost-effective pathway to hydrogen fuel, however, photocatalysts that can compete with the energy conversion efficiency of photovoltaic and photoelectrochemical cells are still lacking. Recently, Goto et al. reported ( Joule, 2018, 2 (3), 509–520) that Al-doped SrTiO3 microparticles, followed by modification with Rh2− y Cr y O3 support overall water splitting with 0.4% solar to hydrogen efficiency and with 56% apparent quantum yield at 365 nm. Earlier, based on transient IR spectroscopy results, the improved activity of Al:SrTiO3 had been attributed to the removal of Ti 3+ deep recombination sites by the Al 3+ ions. Here we use X-ray photoelectron spectroscopy to show that Al 3+ incorporation not only reduces the Ti 3+ concentration but also diminishes the n-type character of SrTiO3 and shifts the Fermi level to more oxidizing potentials. According to DFT, the electronic structure of Al-doped SrTiO3 depends sensitively on the relative locations of Al 3+ and oxygen vacancies sites, with Al 3+ ions next to the oxygen vacancies being most effective at suppressing the sub-band gap states. Reduced hole and electron trapping resulting from the elimination of Ti 3+ states is confirmed by surface photovoltage spectroscopy and electrochemical scans. These findings not only provide an experimental basis for the superior water splitting activity of Al-doped SrTiO3, under ultraviolet and solar irradiation, but they also suggest that aliovalent doping may be a general method to improve the solar energy conversion properties of metal oxides. Additionally, overall water splitting with a type 1 single bed particle suspension 'baggie' reactor under direct sunlight illumination with 0.11% solar to hydrogen efficiency is also demonstrated for the first time. This provides a proof of concept for one of the models in the 2009 US Department of Energy Technoeconomic analysis for photoelectrochemical hydrogen production.